1995
DOI: 10.1111/j.1530-0277.1995.tb01491.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Changes in G Proteins Do Not Mediate Ethanol‐Induced Downregulation of Adenylyl Cyclase in Mouse Cerebral Cortex

Abstract: Our prior work, and the work of others, demonstrated that chronic administration of ethanol to cells in culture or to mice resulted in decreased responsiveness of adenylyl cyclase (EC4.6.1.1) to a number of stimulatory agents. In this study, we substantiated the ethanol-induced changes in cerebral cortical adenylyl cyclase activity in alcohol-tolerant and alcohol-dependent mice, and we examined whether chronic ethanol treatment of mice altered the quantity of heterotrimeric guanine nucleotide-binding regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Studies in cell culture and rat cortex demonstrated that acute ethanol exposure could stimulate AC activity and increase cAMP production [68], while chronic ethanol exposure resulted in AC desensitization in mouse cortex [69,70]. AC sensitivity to ethanol was shown to be isoform-specific in transfected human embryonic kidney (HEK293) cells [71].…”
Section: Upstream Targets Of Ethanol-mediated Modulation Of Crebmentioning
confidence: 99%
“…Studies in cell culture and rat cortex demonstrated that acute ethanol exposure could stimulate AC activity and increase cAMP production [68], while chronic ethanol exposure resulted in AC desensitization in mouse cortex [69,70]. AC sensitivity to ethanol was shown to be isoform-specific in transfected human embryonic kidney (HEK293) cells [71].…”
Section: Upstream Targets Of Ethanol-mediated Modulation Of Crebmentioning
confidence: 99%
“…While acute ethanol exposure enhanced the agonist-stimulated AC catalytic activity, chronic exposure to ethanol produced adaptive changes in AC function both in animals and in cell cultures (Gobejishvili et al, 2006; Hoffman and Tabakoff, 1990; Rabin, 1990). Desensitization of the AC system by long-term exposure to ethanol is heterologous, as the diminished AC activity was observed in response to a variety of activators (Gordon et al, 1986; Richelson et al, 1986; Tabakoff et al, 1995). Despite parallel observations of inhibited neurogenesis and AC system downregulation caused by chronic ethanol exposure, a direct link between ethanol-induced cAMP regulation and neurogenic differentiation has not been clearly established.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, long-term incubation of the NG 108-15 neuroblastoma glioma hybrid cell line with ethanol was not associated with any change in Gia-proteins (Charness et al, 1988). In addition, in vivo studies on chronic ethanol consumption demonstrated no changes in Gi proteins in the cerebral cortex (Tabakoff et al, 1995).…”
Section: Discussionmentioning
confidence: 83%